2023
DOI: 10.3389/fpubh.2023.1035759
|View full text |Cite
|
Sign up to set email alerts
|

Pooled prevalence and determinants of antenatal care visits in countries with high maternal mortality: A multi-country analysis

Abstract: BackgroundComplications during pregnancy and childbirth are the leading causes of maternal and child deaths and disabilities, particularly in low- and middle-income countries. Timely and frequent antenatal care prevents these burdens by promoting existing disease treatments, vaccination, iron supplementation, and HIV counseling and testing during pregnancy. Many factors could contribute to optimal ANC utilization remaining below targets in countries with high maternal mortality. This study aimed to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Similarly, pregnant women from richer households and richest households had fourteen and twenty-four percent more antenatal care visits when compared to women from poor households. The finding is similar to studies conducted in different countries [ 19 , 20 ]. The current study also showed that, compared to women from rural areas, women from urban areas had 61 percent more antenatal care visits.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, pregnant women from richer households and richest households had fourteen and twenty-four percent more antenatal care visits when compared to women from poor households. The finding is similar to studies conducted in different countries [ 19 , 20 ]. The current study also showed that, compared to women from rural areas, women from urban areas had 61 percent more antenatal care visits.…”
Section: Discussionsupporting
confidence: 91%
“…Nationally representative data collected in Ethiopia in 2020 support this (24), a systematic review and meta-analysis carried out in Cameroon (27), the DHS of Sub-Saharan Africa (29), and East African countries (26). This might be a result of the fact that women are more likely to use healthcare services as their experience and knowledge of them grows (32,33).…”
Section: Discussionmentioning
confidence: 96%
“…Age: The expected count of infant deaths for mothers aged less than 19 years and more than 35 years at their first birth is 32% higher than for the reference group (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Again, the risk of infant mortality is 1.27 times higher (e .242 = 1.27, P =.000) https://www.indjst.org/ for mothers aged less than 19 years and more than 35 years at the time of their first birth in the zero inflation group compared to mothers aged (19-35) years.…”
Section: Place Of Residencementioning
confidence: 99%
“…Also, as birth order increases, the quality of child care reduces since the mother will have to care for more children (11) . This may also be attributable to higher confidence from prior pregnancies and delivery experiences with restrictions of time and resources among women who had multiple birth orders (25) . https://www.indjst.org/…”
Section: Level Of Educationmentioning
confidence: 99%